Information Labour and Shame in Farmer and Chevli's Abortion Eve. Issue 1 (3rd April 2019) - McGovern, Melanie; Paul Eve, Martin
Abstract : This article conducts the first in-depth political-aesthetic analysis of Joyce Farmer and Lyn Chevli's Abortion Eve . In this article we argue that Abortion Eve uses its visual form in a way that cuts between the contexts of later forms of graphic medicine and feminist comix, and in so doing contributed to a political culture of feminist information sharing, through a self-published visual medium.